RESERVATION SYSTEMS APPLICATIONS PRODUCTS IN.GEMA INSANI PRESS - Devi Devi; Ire Puspa Wardhani,SKom, MMSI (Jurnal Sistem Informasi, 2001)
Ordering goods transaction activity is still done manually. This of course will require a longer time compared to using the tool, namely the computer. The weaknesses inherent in the current system is the process of ordering goods and a report will be given to the leadership as well as information required by the parties who need them.